Content and Themes of Repetitive Thinking in Postnatal First-Time Mothers - Newby, Jill M.; Werner-Seidler, Aliza; Black, Melissa J.; Hirsch, Colette R.; Moulds, Michelle L. (Frontiers in Psychology, 2021)
Repetitive thinking (RT) predicts and maintains depression and anxiety, yet the role of RT in the perinatal context has been under-researched. Further, the content and themes that emerge during RT in the perinatal period have been minimally investigated. We recruited an online community sample of women who had their first baby within the past 12 months (n = 236). Participants completed a battery of self-report questionnaires which included four open-ended questions about the content of their RT. Responses to the latter were analysed using an inductive thematic analysis approach. Participants reported RT about a range of unexpected emotional responses to becoming a new mother, impact on their sleep and cognitive functioning, as well as the impact on their identity, sense of self, lifestyle, achievements, and ability to function. RT was commonly experienced in first-time mothers, and the themes that emerged conveyed an overall sense of discrepancy between expectations and reality, as well as adjustment to profound change. By providing insight into the content of RT in new mothers, the findings of our study have scope to inform the content of interventions that seek to prevent and treat postnatal mental health problems, particularly those which target key psychological processes such as RT.